Melhoria da qualidade para prevenção de infecção de sítio cirúrgico em pacientes submetidos a cirurgia cardíaca - Oliveira, Maria Aline Gomes de (2023)
Introduction: Surgical site infection is the most common complication resulting from surgery, which occurs in the first 30 - 90 days postoperatively. It is among the main healthcare-associated infections, corresponding to 14 to 16% of those found in hospitalized patients in Brazil. The emergence of these infections in cardiac surgery represents a challenge because it presents a high rate of morbidity and mortality, it is considered an avoidable adverse event that threatens patient safety, in addition to significantly adding to medical-hospital costs, with negative repercussions on care practice. Efforts to reduce the rate of these infectious complications include the integration of a number of preventive measures implemented to treat modifiable risk factors at all operative periods. Objective: To develop an improvement cycle to prevent surgical site infection in adult patients undergoing cardiac surgery and to evaluate the effect of interventions performed in a cardiology referral hospital located in the Northeast region of Brazil. Methodology: This is a quantitative study, with a quasi-experimental before-and-after design, without a control group, carried out in three stages, from March 2022 to March 2023. The first stage consisted of an analysis of non-conformities identified before the interventions of the improvement cycle through data collected from medical records. The second and third stages included a prospective intervention study carried out through the application of a quality improvement cycle. Nine criteria were developed to evaluate the quality of the surgical process and two outcome criteria were developed to analyze improvement. The analysis was performed by calculating the point estimate with a 95% confidence interval, the absolute and relative improvement of each criterion was calculated, and the chi-square test and Fisher's exact test were performed. The level of statistical significance adopted was p-value <0.05. Results: there was a difference between the initial evaluation and the second reassessment in Criteria C1 (bath), C2 (trichotomy), C5 (surgical time), C7 (dressing) and C8 (checklist), with a statistically significant increase in the percentage of compliance. The Pareto Chart before and after showed a frequency of 118 nonconformities in the initial assessment and 58 in the second reassessment. The result of the indicator of incidence of cardiac surgical site infection shows a reduction of 50.8% when compared to the initial evaluation, and the incidence of mediastinitis of 1.38%, which is compatible with the mean within the spectrum reported in the literature. Conclusions: The study proved the importance of applying the improvement cycle as a quality management tool in conjunction with the science of improvement for standardization of care practices, resulting in a reduction in surgical nonconformities, infectious complication rates, and patient safety.